2007
DOI: 10.1088/0953-8984/19/14/145279
|View full text |Cite
|
Sign up to set email alerts
|

Control of the ferroelectricity in a metastable state for orthorhombicRMnO3crystals

Abstract: We have investigated orthorhombic RMnO 3 (R=(Gd 1−y Tb y )) crystals near the phase boundary between the paraelectric A-type-antiferromagnetic (AF) phase (PA) and the ferroelectric transverse-spiral-AF one (FS). The spiral AF structure breaks inversion symmetry and induces the ferroelectric polarization through the inverse Dzyaloshinskii-Moriya (DM) interaction. We have found that the PA-FS phase boundary is located at around 0.15 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Let us move on to the magnetic field effect on the ferroelectricity. As already reported in our previous reports [7,8,9] and other groups' [1, 2, 10], the magnetic field along the b axis (H b ) stabilizes the ferroelectric phase. The observed ferroelectric transition temperatures are drastically increased by application of H b , as shown in the Fig.…”
Section: Resultssupporting
confidence: 70%
“…Let us move on to the magnetic field effect on the ferroelectricity. As already reported in our previous reports [7,8,9] and other groups' [1, 2, 10], the magnetic field along the b axis (H b ) stabilizes the ferroelectric phase. The observed ferroelectric transition temperatures are drastically increased by application of H b , as shown in the Fig.…”
Section: Resultssupporting
confidence: 70%
“…Recently, new interesting properties of some RMnO 3 manganites have been revealed which are related to a change of their magnetic structure from a canted antiferromagnetic layer ordering (A y F z ) to a spatially modulated (sinusoidal) antiferromagnetic one for R = Eu, Gd, Tb, Dy caused by a frustration of exchange interactions due to decreasing of the R-ionic radii r R from La to Dy [1][2][3][4][5][6]. It results in the appearance of electric polarization below the spontaneous incommensurate-commensurate (IC-C) transition at temperature T lock < T N = 45 -40 K and unusual magnetic-field-induced transitions accompanied by reorientation or suppression of electric polarization for R = Tb, Dy [1,2] and Gd [7,8]. In this work we have realized the above-mentioned tendency to form multiferroic states in the substituted compounds Eu 1-x Y x MnO 3 and Gd 1-y Y y MnO 3 , where an average r R and parameters of Mn-O-Mn bonds are continuously adjusted by the content of Y with a smaller ionic radii thus permitting a gradual control of magnetic and electric ground states.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the magnetic ferroelectricity has been reported at the IC-C (lock-in) magnetic transition temperature in TbMn03 [3]. Recently, we have found that the ferroelectric phase exists below 13K in the A-type AF GdMn03 crystal [4] [5]. The spontaneous polarization was confirmed to be present along a axis in the orthorhombic Pbnna setting.…”
Section: Introductionmentioning
confidence: 91%